2023
DOI: 10.3390/molecules28041762
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of the Antibiotics Approved in the Last Two Decades: Retrospects and Prospects

Abstract: Due to the overuse of antibiotics, bacterial resistance has markedly increased to become a global problem and a major threat to human health. Fortunately, in recent years, various new antibiotics have been developed through both improvements to traditional antibiotics and the discovery of antibiotics with novel mechanisms with the aim of addressing the decrease in the efficacy of traditional antibiotics. This manuscript reviews the antibiotics that have been approved for marketing in the last 20 years with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 199 publications
0
11
0
Order By: Relevance
“…These molecules include trovafloxacin, tosufloxacin, and sitafloxacin. Enrofloxacin was selected for inclusion based on its previous use in in vitro research, along with its high bioavailability and low toxicity [ 36 ]. Furthermore, prulifloxacin ( Figure S2 ) was included in the study due to its structural feature of a four-membered ring containing a sulfur atom, which has been reported to enhance its activity [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…These molecules include trovafloxacin, tosufloxacin, and sitafloxacin. Enrofloxacin was selected for inclusion based on its previous use in in vitro research, along with its high bioavailability and low toxicity [ 36 ]. Furthermore, prulifloxacin ( Figure S2 ) was included in the study due to its structural feature of a four-membered ring containing a sulfur atom, which has been reported to enhance its activity [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adverse reactions of the intervention mainly involve gastrointestinal, hepatic, cardiac, hematologic, and neurological-related symptoms [ 23 ]. It was observed that the most frequent adverse event in the gastrointestinal system was nausea, as reported by all four RCTs [ 14 - 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Tigecycline, a potent antibiotic within the tetracycline family, has long faced a significant challenge in clinical administration due to its poor stability. 1 Susceptibility to oxidation and nonenzymatic epimerization, especially at higher pH values, has restricted its usage in ambulatory settings and limited exploration into its potential antileukemic activity. 2 In response to these challenges, a groundbreaking formulation has been developed, promising to extend tigecycline's stability after reconstitution and open new avenues for clinical applications.…”
Section: Introductionmentioning
confidence: 99%